Public service ethics, values and spirituality in developing and transitional countries: Challenges and opportunities. (21st September 2020) - Hossain, Farhad; Kumasey, Anthony Sumnaya; Rees, Christopher J.; Mamman, Aminu
Summary: Concerns over the unethical conduct of leaders and public officials have led to the renaissance of interest in public service ethics and values. Although national and organizational systems and structures have been instituted to either eradicate or ameliorate unethical behaviours in the public service of countries, the practice still persists with devastating consequences. As one way forward, spirituality has been touted as having the potential of stimulating the moral thoughts of individuals who are dealing with ethical issues, thereby reducing unethical behaviour and generating positive organizational behaviour. Drawing from the perspectives of developing and transitional countries, this special issue empirically examines the extent to which ethics, values and spirituality can reduce unethical behaviours.